Foreign trade relations between Russia and Armenia: features and trends - E. R. Ablitarov; A. O. Kaminskaya (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the foreign trade relations of the Russian Federation and the Republic of Armenia in modern conditions. The analysis of the dynamics of foreign trade between Russia and Armenia for 2014–2021 is carried out. An overview of the structure of exports and imports of Russia and Armenia for 2014 and 2021 is given. The factors influencing the foreign trade activity between the countries are identified. Special attention is paid to the geopolitical and geo-economic aspects of foreign trade cooperation. The role of integration processes within the framework of the Eurasian Economic Union (hereinafter referred to as the EAEU) in the development of trade and economic relations between the countries is considered. The main directions of interregional cooperation defined in the Development Program for 2022-2027 are highlighted. The effectiveness of the existing mechanisms of trade and economic cooperation is assessed and recommendations are proposed for further strengthening foreign trade relations between the Russian Federation and the Republic of Armenia in the context of the geopolitical situation and global economic trends.